Analysis Of Prodyction Costs And Cost Of Production On The Selling Price Of Water Madina Murni Mandailng Natal - Khoirun Nisa; Nur Fadhilah Ahmad Hasibuan (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The purpose ofuthis research is to find out how the company determines the cost of production, and how the pricing of goods manufactured affect the selling price of products. AMDK (Drinking Water Packaging) ucompany Madin Murni Inc. In determining the base cost of production and sellinguprice was nott yet counting carefully. In determininguthe sale price of AMDK Madina Murni Inc. was not yet appropriate, the company set the sale price based on the management's decision. In the production process, the company would issue costs starting from manufacturing to producing the finished goods which were ready forusale. The method used inuthis study is the interviews conducted with financial managers, preparers of financial statements, production and sales. In addition to interviews also by analyzing the financial lapporan related to costs of production. The resultsuof this study indicated that Madina Murni Inc. had its own way inucalculatinguproductionucost, that is, by charging electricityucostuasuwelluas shrinkage. In addition, in calculating the production cost it was only labor cost, raw water cost, operatingucost, maintenanceucost, packaging cost, and laboratory cost that were charged too.